At the frontiers of cycling. Policy innovations in the Netherlands, Denmark, and Germany. - Pucher, John; Buehler, Ralph (My University, 2007)
This article presents six detailed case studies of cycling in the Netherlands (Amsterdam and Groningen), Denmark (Copenhagen and Odense), and Germany (Berlin and Muenster). Except for Berlin, they represent the very best in coordinated policies and programs to make cycling safe, convenient, and attractive. Not only are cycling levels extraordinarily high in these cities, but virtually everyone cycles: women as well as men, the old and the young, the rich and the poor. Moreover, they cycle for a wide range of daily, practical trips purposes and not mainly for recreation. Berlin is a special case. It does not even approach the five other cities in their cycling orientation. Nevertheless, its recent measures to encourage cycling have achieved an impressive bike share of trips for such a large city, higher than any other European city of that size. Thus, all six of the bicycling case study cities examined in this article truly are at the frontiers of cycling. They have many lessons to offer other cities in the Western World about the best ways to encourage more cycling. difu
Keywords: Fahrradverkehr; Verkehrspolitik; Vergleich; Fallstudie; Verkehrsmittelwahl; Verkehrsverhalten; Bevölkerungsstruktur; Verkehrssicherheit; Erhebung; Individualverkehr; Fahrradförderung; Fahrradnutzung; Radverkehrsanteil; Fahrradinfrastruktur; Radverkehrsanlage